3D pore structure and mass transport properties of blended cementitious materials. (March 2019) - Yio, M.H.N.; Wong, H.S.; Buenfeld, N.R.
Abstract: The effect of supplementary cementitious materials on three-dimensional pore structure and how this influences mass transport properties are not well understood. This paper examines the effect of silica fume, fly ash and ground granulated blastfurnace slag on 3D structure of capillary pores (>0.24 μm) within 100 3  μm 3 cement paste for the first time using laser scanning confocal microscopy, combined with backscattered electron imaging and mercury intrusion porosimetry. Pastes containing different binder types, w/b ratios and curing ages were tested. Results show that SF enhances 3D pore structure from early ages whereas PFA and GGBS show improvements at later ages. SCMs not only reduce the volume and size of accessible pores, but also decrease connectivity and increase tortuosity, pore coordination number and formation factor. Measured 3D pore parameters were used as modelling inputs to estimate diffusivity and permeability. Predictions to within a factor of five from measured values were obtained.